Some synonymous and nonsynonymous gyrA mutations in Mycobacterium tuberculosis lead to systematic false-positive fluoroquinolone resistance results with the Hain GenoType MTBDRsl assays - Ajileye, A; Alvarez, N; Merker, M; Walker, T; Akter, S; Brown, K; Moradigaravand, D; Schön, T; Andres, S; Schleusener, V; Omar, S; Coll, F; et al. (American Society for Microbiology, 2017)
In this study, using the Hain GenoType MTBDRsl assays (versions 1 and 2), we found that some nonsynonymous and synonymous mutations in gyrA in Mycobacterium tuberculosis result in systematic false-resistance results to fluoroquinolones by preventing the binding of wild-type probes. Moreover, such mutations can prevent the binding of mutant probes designed for the identification of specific resistance mutations. Although these mutations are likely rare globally, they occur in approximately 7% of multidrug-resistant tuberculosis strains in some settings.